Análisis de la arquitectura OSGI en el desarrollo de sistemas informáticos modulares basado en el servicio aplicado a un sistema parametrizable que provea información relacionada con la evaluación de carreras en la Universidad Nacinal de Chimborazo en el perodo 2011-2012 - Naranjo Delgado, Catherine Alexandra (2012)
This study aims to determine the importance of applying OSGi architecture in developing modular systems based on services. According to the architecture analysis and in contrast with systems developed without OSGi architecture, through comparison indicators: modularity, reusability and complexity in development, which are requirements or characteristics of modular systems development, it is determined that the use of OSGi architecture is 90% effective for the development of modular systems based on services, attributing not only logical modularity but also physical modularity, while other forms of development without the architecture are 10% efficient allowing a system be modular only in logic form.